Free all along : the Robert Penn Warren civil rights interviews - Smith, Stephen, 1960-; Ellis, Catherine, 1964-; Warren, Robert Penn, 1905-1989 (The New Press, 2019)
"A collection of previously unpublished interviews with key figures of the black freedom struggle by Pulitzer Prize-winning author Robert Penn Warren"--